Heat and mass transfer in an adsorption panel with rod fins heated by a radiant source 3D mathematical model - De Leon, Rizalinda; Cortes, Arturo B.; Chu, Richard Q.
A 3-D modified equilibrium, static-bed model of adsorption in an adsorption panel with rod fins heated by a radiant heat source is developed and solved using the Method of Lines. The energy equation is transformed to have only one dependent variable hence the accumulation, conduction and generation terms are all expressed in terms of rate of change and gradient of the local bed temperature. Results are compared with experimental data for insight into the heat and mass transfer process occurring in the bed during the cooling and heating process. Effective surface diffusivities derived agree with literature values obtained by other authors.
Keywords: Diffusivity; Effective thermal conductivity; Method of lines